Modeling of Liquefaction using Two-phase FEM with UBC3D-PLM model. (2017) - Wobbes, Elizaveta; Beuth, Lars; Vuik, Cornelis; Stolle, Dieter
Abstract: Soil liquefaction describes a loss of strength of saturated sand upon sudden or cyclic loading. A slight disturbance of such a soil's fabric might lead to severe damage, e.g. the collapse of sea dikes. Accurate modeling of the state transition between saturated soil and a liquefied soil-water mixture, as well as post-liquefaction phenomena, is crucial for the prediction of such damage. However, developing an appropriate numerical model remains a challenging problem, especially when the simulation involves dynamic large deformation processes. In order to make a first step towards an accurate simulation of soil liquefaction, a two-phase formulation of the finite element method (FEM) in conjunction with the elastoplastic UBC3D-PLM model is investigated. The performance of this approach is analyzed based on a shaking table benchmark.